On the real effects of the monetary policy: A central banker's view - Javier Valles; Jose Vinals (Oesterreichische Nationalbank (OeNB), 1999)
This paper deals with an old issue which nevertheless continues to be of great relevance for central bankers: the impact of monetary policy on the economy. The empirical evidence discussed in the paper suggests that since, over the medium term, inflation is primarily a monetary phenomenon and entails significant economic costs, the best contribution that monetary policy can make to society's welfare is to maintain price stability. Still, over the short-term, monetary policy seems to affect real economic variables regardless of whether policy moves are systematic responses to the state of the economy or exogenous shocks, presumably as a result of the coexistence of nominal and real rigidities. While these general results appear quite reasonable, beyond this it would be much harder to find any agreement concerning what the precise timing and magnitudes of the output and price effects of monetary policy are over the short-term. From a central banker's viewpoint, a sensible reading of the evidence would be that while the medium-term monetary stance must be set consistently with the maintenance of price stability, this does not preclude central banks prudently exercising a certain margin of flexibility to respond to macroeconomic disturbances in the short-run, provided this does not jeopardize the primary goal of price stability. Finally, our discussion of the potential uncertainties surrounding the impact of monetary policy in a low inflation, low interest rate environment -like that prevailing today in many countries and economic areas- reaches the highly tentative conclusion that a monetary policy easing may become less effective in promoting economic activity in that context, even when such a move does not place at risk the maintenance of price stability. An implication of the above would be that, in the present circumstances, monetary policy should not be overburdened with the responsibility of solving problems which are better tackled through other policies which directly aim at improving the functioning of the economy.
Keywords: 330; monetary policy; central banking; price stability